An experimental investigation of the effect of specimen shape and geometry on the energy absorption of fiberglass composite tubes - Abdewi , Elfetori F.; Sulaiman, Shamsuddin; Hamouda , Abdel Majid Salem; Ebrahimi, Mahdi (Universiti Putra Malaysia Press, 2005)
The purpose of this work is to investigate the effect of the dimensions of composite tubes on their specific energy absorption capacity. Experimental investigations were carried out on three geometrical different cylindrical composite tubes subjected to compressive loading. More over a radial corrugated composite tube was subjected to the same load conditions in order to examine the varying of shape influence on the energy absorption of composite materials. Initial results indicate that for cylindrical tubes, diameter to thickness ratio has a significant effect on the energy absorption. Reduction in tube d/t ratio results in an increase in energy absorption. More over results show also radial corrugated composite tubes exhibit higher total energy absorption than cylindrical composite tubes.